Laminin-10 is crucial for hair morphogenesis - Li, Jie (Oxford University Press, 2003)
The role of the extracellular matrix in cutaneous morphogenesis is poorly understood. Here, we describe the essential role of laminin-10 (α5β1γ1) in hair follicle development. Laminin-10 was present in the basement membrane of elongating hair germs, when other laminins were downregulated, suggesting a role for laminin-10 in hair development. Treatment of human scalp xenografts with antibodies to laminin-10, or its receptor β1 integrin, produced alopecia. E16.5 Lama5 –/– mouse skin, lacking laminin-10, contained fewer hair germs compared with controls, and after transplantation, Lama5 –/– skin showed a failure of hair germ elongation followed by complete hair follicle regression. Lama5 –/– skin showed defective basement membrane assembly, without measurable increases in anoikis. Instead, Lama5 –/– skin showed decreased expression of early hair markers including sonic hedgehog and Gli1, implicating laminin-10 in developmental signaling. Intriguingly, treatment of Lama5 –/– skin with purified laminin-10 corrected basement membrane defects and restored hair follicle development. We conclude that laminin-10 is required for hair follicle development and report the first use of exogenous protein to correct a cutaneous developmental defect.